Analysis of Thalut's Leadership Style as Inspiration for Gen Z in Choosing Leaders - Sarah Mitha Amelia; Ali Akbar (Yayasan Adra Karima Hubbi, 2024)
Background. Leadership is a person's ability to motivate others to work toward a common goal. Effective leaders have good knowledge and skills in building solid relationships in a positive environment and have the ability to manage conflict. The story of Thalut in Surah Al-Baqarah of the Qur'an serves as an inspiration for selecting leaders based on qualifications and expertise. Purpose. This research, It’s not only emphasizes the importance of leadership based on knowledge and skills, but also reminds us of the values that are relevant in today's context, especially for Gen-Z, which is beginning to replace the millennial era. Method. This study employs a literature review approach, utilizing qualitative descriptive-analytical methods. It first investigates sources related to Thalut as mentioned in the Qur'an, along with other literature such as Hadith and Tafsir texts. The research then compiles various data reflecting Gen Z's attitudes and behaviors concerning leadership selection. Finally, the collected data is systematically analyzed to extract meaningful insights and applications. Results. This research aim of this research is to provide inspiration for Gen Z in their approach to selecting leaders. By highlighting the admirable qualities of Thalut, such as integrity and the ability to unite others, this study encourages Gen Z to seek leaders who are not only skilled but also deeply committed to making a positive impact in their communities. Conclusion. In conclusion, the leadership qualities demonstrated by Thalut serve as a significant model for today's leaders. By embracing the principles embodied by Thalut—such as integrity, knowledge, and conflict resolution—Gen Z can make informed and responsible choices in their leadership selections. This approach not only nurtures effective leaders but also empowers a generation ready to confront modern challenges with confidence and purpose.